2011
DOI: 10.4315/0362-028x.jfp-10-497
|View full text |Cite
|
Sign up to set email alerts
|

Assumptions of Acceptance Sampling and the Implications for Lot Contamination: Escherichia coli O157 in Lots of Australian Manufacturing Beef

Abstract: The aims of this work were to determine the distribution and concentration of Escherichia coli O157 in lots of beef destined for grinding (manufacturing beef) that failed to meet Australian requirements for export, to use these data to better understand the performance of sampling plans based on the binomial distribution, and to consider alternative approaches for evaluating sampling plans. For each of five lots from which E. coli O157 had been detected, 900 samples from the external carcass surface were teste… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
21
1

Year Published

2011
2011
2021
2021

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 18 publications
(23 citation statements)
references
References 11 publications
1
21
1
Order By: Relevance
“…However, for the purpose of this risk assessment it was assumed that contaminated lots were not removed from the export supply chain due to N-60 testing at the processing plant and were shipped to the United States for grinding into patties. In addition, it was assumed that the contaminated lots that were detected during routine export certification testing (16) are representative of all other contaminated lots.…”
Section: Exposure Assessmentmentioning
confidence: 99%
See 3 more Smart Citations
“…However, for the purpose of this risk assessment it was assumed that contaminated lots were not removed from the export supply chain due to N-60 testing at the processing plant and were shipped to the United States for grinding into patties. In addition, it was assumed that the contaminated lots that were detected during routine export certification testing (16) are representative of all other contaminated lots.…”
Section: Exposure Assessmentmentioning
confidence: 99%
“…Previous work indicated that only a small fraction (0.5%) of Australian lots are likely contaminated with E. coli O157. (16) Hence, the efficiency of simulation could be improved by only simulating contaminated lots. This was done because uncontaminated lots do not add to the risk (constant risk that equals zero); however, the fraction of contaminated lots is taken into account for the calculation of final risk estimates.…”
Section: Exposure Assessmentmentioning
confidence: 99%
See 2 more Smart Citations
“…Investigation of Australian manufacturing beef in which E. coli O157 had been detected (and removed from the food chain) indicates that, when E. coli O157 is detected it is not widespread through the lot and is at low concentration (Kiermeier, Mellor, Barlow, & Jenson, 2011). From these data, one would suspect a very low risk of consumers being affected.…”
Section: Performance Standards In the Time Of Diminishing Returnsmentioning
confidence: 96%